2017
DOI: 10.1167/tvst.6.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Embryonic Stem Cell-Derived Retinal Cells into the Subretinal Space of a Non-Human Primate

Abstract: PurposePrevious studies have demonstrated the ability of retinal cells derived from human embryonic stem cells (hESCs) to survive, integrate into the host retina, and mediate light responses in murine mouse models. Our aim is to determine whether these cells can also survive and integrate into the retina of a nonhuman primate, Saimiri sciureus, following transplantation into the subretinal space.MethodshESCs were differentiated toward retinal neuronal fates using our previously published technique and cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 38 publications
0
56
0
1
Order By: Relevance
“…The capacity to generate bona fide fetal-stage neural retinal cell types and tissues from human embryonic and induced pluripotent stem cells (hESCs and hiPSCs; collectively, hPSCs) has spurred their use in disease modeling (Tucker et al, 2011(Tucker et al, , 2013Jin et al, 2012;Phillips et al, 2014;Yoshida et al, 2015;Arno et al, 2016;Parfitt et al, 2016;Megaw et al, 2017;Schwarz et al, 2017;Sharma et al, 2017;Shimada et al, 2017;Deng et al, 2018) and photoreceptor (PR) replacement efforts (Lamba et al, 2009(Lamba et al, , 2010Hambright et al, 2012;Barnea-Cramer et al, 2016;Shirai et al, 2016;Chao et al, 2017;Gonzalez-Cordero et al, 2017;Mandai et al, 2017;Zhu et al, 2017Zhu et al, , 2018Iraha et al, 2018;Lakowski et al, 2018;McLelland et al, 2018;Gagliardi et al, 2018). Most of these studies employ hPSC differentiation methods that propagate retinal progeny as isolated 3D optic vesicle-like structures (OVs), also known as retinal organoids, in suspension culture (Meyer et al, 2009(Meyer et al, , 2011Nakano et al, 2012;Phillips et al, 2012Phillips et al, , 2018bSridhar et al, 2016;Reichman et al, 2014;Zhong et al, 2014;Kuwahara et al, 2015;Mellough et al, 2015;Singh et al, 2015;Lowe et al, 2016;…”
Section: Introductionmentioning
confidence: 99%
“…The capacity to generate bona fide fetal-stage neural retinal cell types and tissues from human embryonic and induced pluripotent stem cells (hESCs and hiPSCs; collectively, hPSCs) has spurred their use in disease modeling (Tucker et al, 2011(Tucker et al, , 2013Jin et al, 2012;Phillips et al, 2014;Yoshida et al, 2015;Arno et al, 2016;Parfitt et al, 2016;Megaw et al, 2017;Schwarz et al, 2017;Sharma et al, 2017;Shimada et al, 2017;Deng et al, 2018) and photoreceptor (PR) replacement efforts (Lamba et al, 2009(Lamba et al, , 2010Hambright et al, 2012;Barnea-Cramer et al, 2016;Shirai et al, 2016;Chao et al, 2017;Gonzalez-Cordero et al, 2017;Mandai et al, 2017;Zhu et al, 2017Zhu et al, , 2018Iraha et al, 2018;Lakowski et al, 2018;McLelland et al, 2018;Gagliardi et al, 2018). Most of these studies employ hPSC differentiation methods that propagate retinal progeny as isolated 3D optic vesicle-like structures (OVs), also known as retinal organoids, in suspension culture (Meyer et al, 2009(Meyer et al, , 2011Nakano et al, 2012;Phillips et al, 2012Phillips et al, , 2018bSridhar et al, 2016;Reichman et al, 2014;Zhong et al, 2014;Kuwahara et al, 2015;Mellough et al, 2015;Singh et al, 2015;Lowe et al, 2016;…”
Section: Introductionmentioning
confidence: 99%
“…Aktuell laufen erste klinische Studien dazu im Kontext der Glaukomerkrankung. Die Verwendung transplantierter Ganglionzellen oder der kontrovers diskutierte Einsatz humaner embryonaler Stammzellen beinhaltet vermutlich ebenso ein hohes Potenzial zum Ersatz untergegangener Nervenzellen der Retina, wie bereits an adulten Ratten sowie nicht menschlichen Primaten histologisch und elektrophysiologisch gezeigt werden konnte [32,33]. Weitere Ansätze zur Prävention neurodegenerativer Prozesse der Retina und des N. opticus untersuchen Faktoren, wie die überwiegend über NMDA-Rezeptoren-vermittelte Glutamat-Exzitotoxizität (über Blockade dieses Rezeptors) oder eine Verbesserung des Energiemetabolismus bspw.…”
Section: Weitere Ansätzeunclassified
“…14 Photoreceptor generation from hESCs has progressed more rapidly than has generation of RGCs. 94,95 Whilst hESC technology is in essence still embryonic, with ethical and scientific challenges, it has the potential to revolutionalize the management of ocular neurodegenerative disease considered incurable through neuroregeneration of functioning retinal neurons. 49 Preclinical studies (in mature uninjured rat and monkey eyes) have previously demonstrated the ability of retinal cells derived from hESCs to survive, integrate into the host retina and mediate light responses.…”
Section: Human Embryonic Stem Cellsmentioning
confidence: 99%
“…49 Preclinical studies (in mature uninjured rat and monkey eyes) have previously demonstrated the ability of retinal cells derived from hESCs to survive, integrate into the host retina and mediate light responses. 94,95 Whilst hESC technology is in essence still embryonic, with ethical and scientific challenges, it has the potential to revolutionalize the management of ocular neurodegenerative disease considered incurable through neuroregeneration of functioning retinal neurons.…”
Section: Human Embryonic Stem Cellsmentioning
confidence: 99%